Banana weevil, Cosmopolites sordidus (Germar), ovipositional preferences, timing of attack and larval survivorship in a mixed cultivar trial in Uganda - Abera, A.; Kyamanywa, S.; Karamura, E.B. (2000)
Host location, acceptance and larval success were studied in a mixed cultivar trial consisting of three East African cooking bananas, two East African beer banana and Kayinja (an exotic cultivar used for beer making). Weevil damage to the endemic cultivars was 5 to 25 times higher than that of Kayinja. Capture of weevils in pseudostem traps at the base of banana mats was highest for Kayinja, while egg density on Kayinja was similar to that of four endemic cultivars. Therefore, host location and acceptance do not appear to be factors in host plant resistance. In contrast, larval survivorship indices were 10 to 23 times higher in endemic cultivars than in Kayinja suggesting that larval success may be an important factor in resistance to banana weevils. Timing of attack was similar among cultivars. Oviposition occurred throughout the banana cycle with egg density increasing with plant age. These data provide a possible explanation of differences in weevil attack found among banana cultivars in Uganda.